Quantitative proteomic analysis of trypsin-treated extracellular vesicles to identify the real-vesicular proteins - Choi, Dongsic (J Extracell Vesicles, 2020)
Extracellular vesicles (EVs) are nano-sized vesicles surrounded by a lipid bilayer and released into the extracellular milieu by most of cells. Although various EV isolation methods have been established, most of the current methods isolate EVs with contaminated non-vesicular proteins. By applying the label-free quantitative proteomic analyses of human colon cancer cell SW480-derived EVs, we identified trypsin-sensitive and trypsin-resistant vesicular proteins. Further systems biology and protein–protein interaction network analyses based on their cellular localization, we classified the trypsin-sensitive and trypsin-resistant vesicular proteins into two subgroups: 363 candidate real-vesicular proteins and 151 contaminated non-vesicular proteins. Moreover, the protein interaction network analyses showed that candidate real-vesicular proteins are mainly derived from plasma membrane (46.8%), cytosol (36.6%), cytoskeleton (8.0%) and extracellular region (2.5%). On the other hand, most of the contaminated non-vesicular proteins derived from nucleus, Golgi apparatus, endoplasmic reticulum and mitochondria. In addition, ribosomal protein complexes and T-complex proteins were classified as the contaminated non-vesicular proteins. Taken together, our trypsin-digested proteomic approach on EVs is an important advance to identify the real-vesicular proteins that could help to understand EV biogenesis and protein cargo-sorting mechanism during EV release, to identify more reliable EV diagnostic marker proteins, and to decode pathophysiological roles of EVs.